Oceanographic Research. - WOODS HOLE OCEANOGRAPHIC INSTITUTION MASS (1950)
This report contains a quarterly summary of work carried out by the Woods Hole Oceanographic Institution under the following headings: Papers Published; Papers Submitted for Publication; Papers Presented at American Society of Limnology and Oceanography; Oceanographic Surveys off East Coast of U.S. between Miami, Florida, and Cape Hatteras; Arctic Oceanography; Salinity Titrations and Calibrations of Thermometers; Sea Surface Wave Studies; Unattended Oceanographic Instruments; Electrokinetograph Cruise; Multiple Sea Sampler; Assistance to Hydrographic Office; Assistance to Naval Research Laboratory, and Personnel. (Author)